Selection for narrow gate of emergence results in correlated sex-specific changes in life history of Drosophila melanogaster - Vishwanath Varma; Nisha N. Kannan; Vijay Kumar Sharma (Biology Open, 2014)
Since the ability to time rhythmic behaviours in accordance with cyclic environments is likely to confer adaptive advantage to organisms, the underlying clocks are believed to be selected for stability in timekeeping over evolutionary time scales. Here we report the results of a study aimed at assessing fitness consequences of a long-term laboratory selection for tighter circadian organisation using fruit fly Drosophila melanogaster populations. We selected flies emerging in a narrow window of 1 h in the morning for several generations and assayed their life history traits such as pre-adult development time, survivorship, adult lifespan and lifetime fecundity. We chose flies emerging during the selection window (in the morning) and another window (in the evening) to represent adaptive and non-adaptive phenotypes, respectively, and examined the correlation of emergence time with adult fitness traits. Adult lifespan of males from the selected populations does not differ from the controls, whereas females from the selected populations have significantly shorter lifespan and produce more eggs during their mid-life compared to the controls. Although there is no difference in the lifespan of males of the selected populations, whether they emerge in morning or evening window, morning emerging females live slightly shorter and lay more eggs during the mid-life stage compared to those emerging in the evening. Interestingly, such a time of emergence dependent difference in fitness is not seen in flies from the control populations. These results, therefore, suggest reduced lifespan and enhanced mid-life reproductive output in females selected for narrow gate of emergence, and a sex-dependent genetic correlation between the timing of emergence and key fitness traits in these populations.